Marketing Strategy of Organizations of Consumer Cooperation Based on the Formation of the Marketing Information System as the Foundation for Ensuring Their Competitiveness - Elena ISAENKO; Е.Е. TARASOVA; N.A. PLETNEVA; L.A. LIBRAM; K.V. TARASOVA (Communications of International Proceedings, 2020)
The purpose of this article is to develop recommendations for implementing the marketing strategy of organizations of consumer cooperation following the formation of the marketing information system for ensuring their competitiveness. The article discusses the essence of the organization’s marketing strategy and the main stages of its formation; the components of the organization’s marketing strategy were selected; the role of the marketing information system for developing and implementing of the marketing strategy is shown; the competitive advantages of organizations of consumer cooperation from the standpoint of their marketing strategies are identified; and strategic directions for retail trade development within consumer cooperation are shown. In the process of research, an algorithm for the organization’s marketing strategy development by means of using a marketing information system is proposed; the conceptual diagram of the organization’s marketing information system formation is given; factors of macro- and microenvironment are studied; SWOT analysis aimed at the expansion of information base for making managerial decisions is carried out; grouping of the consumer cooperation benefits is carried out in accordance with the identified strategies with a view to their use for marketing strategies developing. The article presents a model for marketing strategies formation that allows to track the sequence of operations from setting goals to adjusting the strategy and contribute to the achievement of sustainable competitive positions and rise in the consumer’s loyalty. The article contains a system of assessment indicators and presents the results of a comprehensive assessment of the retail strategies implementation within consumer cooperation under the selected components. The information base for research comprised official statistics, publications on retail trade and consumer cooperation development, marketing researches, as well as source materials collected during the authors’ interviews with customers and heads of organizations of consumer cooperation.
Keywords: Marketing strategy; marketing information system; organizations of consumer cooperation; competitiveness; retail trade; algorithm for marketing strategy development; comprehensive assessment of marketing strategies implementation.